Determinant Factors Brand Loyalty of Tokopedia - Reza Yonatan Hanata; Hendy Tannady; Nanny Mayasari; Jefriyanto; Muhamad Al Faruq Abdullah (Jurnal Multidisiplin Madani, 2023)
The objective of this research is to identify and analyze the effect of Brand Awareness, Brand Association and Corporate Image on Brand Loyalty using a quantitative descriptive approach. The data in this study were obtained from 156 respondents who are Tokopedia users. Data analysis used multiple linear regression and path analysis. The first stage in this study was to test the validity for each variable along with its reliability. The second stage examines the relationship between variables, namely Brand Awareness, Brand Association and Corporate Image with Brand Loyalty. The results of this study is variable Brand Awareness has an effect on Brand Loyalty, Brand Association has an effect on Brand Loyalty, Corporate Image has an effect on Tokopedia Brand Loyalty